Cut-off Value for Stenosis Ratio and Zung Depression Scale in Successful Prediction of Posterior Spinal Fusion surgery - Babaee, Mahsa; Zali, Alireza; Sepehri, Mohammad Mehdi; Razzaghi, Zahra (International Clinical Neuroscience Journal, 2018)
Background: The aim of this study was to investigate effect of some clinical attributes in prediction of satisfaction with posterior spinal fusion (PSF) surgery in patients with lumbar disc herniation (LDH) and lumbar spinal canal stenosis (LSCS) and determine a cut-off point for these attributes. Methods: The attributes such as stenosis ratio (SR) values (described by Lurencin), Japanese Orthopaedic Association (JOA), The Zung depression scale (ZDS), duration of symptoms (in months), were investigated for 329 patients with LSCS and 151 patients with LDH separately. Patient satisfaction was recorded based on the international standard questionnaire Swiss Spinal Stenosis Score (SSS). The sensitivity and specificity values and the optimal cut-off points were calculated for SR, JOA, ZDS and duration of symptoms using receiver operating characteristic (ROC) analysis. Results: One hundred fifty-one patients with LDH (39 male, 112 female; mean age 50.24 ± 9.21 years) and 329 patients with LSCS (111 male, 218 female; mean age 53.28 ±7.81 years) were followed–up for 6 months. Post-surgical satisfaction was 73.86% in patients with LSCS and 85.43% in patients with LDH. The cut-off point of SR for prediction of besting surgical outcome was estimated more than 0.46 with asymptotic significance less than 0.05, 60% sensitivity and 75% specificity in LSCS patients (AUC-0.705, 95% CI, 0.644–0.766; P < 0.001). Conclusion: The findings show that the SR with a cut off value of 0.46 cross sectional area, in patients with LSCS may be superior to JOA, duration of symptoms and ZDS for prediction of satisfaction with PSF surgery.